A history of the Tonga people's relocations from Binga to settlement in Kana Valley - Manika, Tendai (Midlands State University, 2017)
The research examines the History of Tonga relocation from Binga, it pays particular attention to the reasons behind their movement, the various settlements they established and the reasons behind the abandonment of the settlements. The study will focus on Tonga settlement in Kana valley and highlight on the social, cultural and economic activities of the group. The study will also highlight on the arrival of the Karanga into Kana valley and the reasons behind their evictions from Rhodesdale, then take a swipe at the relations between the two groups. The researcher intends to highlight how the autochthones were forced to abandon their lifestyle and conform to Karanga practices .Colonial policies and their biases towards the Karanga will also be highlighted together with the positive and negative effects of Karanga resettlement in the area. Tonga reactions to the new practices and ideas are going to be discussed. The study concludes by focusing on the impacts of Karanga resettlement into the area and shows how the autochthones lost their identity, legacy and heritage. Both primary and secondary sources were used during the study and they made the study a complete product.